Russischer Faust und Hamlet zur Subjektivismuskritik und Intertextualitaet bei I. S.Turgenev - Rothkoegel, Anna (Vortraege und Abhandlungen zur Slavistik, 1998)
I. S. Turgenev's predilection for the use of quotes, but also for allusions to other arts, such as painting or music, is not to be overlooked. Recent research has repeatedly pointed to the intertextuality of Turgenev. The novella "Faust" and the sketch "Gamlet Ščigrovskogo uezda" from the cycle "Zapiski ochotnika" are suitable objects of investigation inasmuch as they have significant similarities both in their intertextuality and in the structure of the text. The parallels begin with the clear marking of the intertextual reference in the title and range from similarities in the narrative form to thematic and argumentative equivalences.